2017
DOI: 10.1515/aiht-2017-68-2989
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of organophosphorus pesticides on the liver: a brief summary of four decades of research

Abstract: Organophosphorus pesticides (OPs) are widely used volatile pesticides that have harmful effects on the liver in acute and chronic exposures. This review article summarises and discusses a wide collection of studies published over the last 40 years reporting on the effects of OPs on the liver, in an attempt to propose general mechanisms of OP hepatotoxicity and possible treatment. Several key biological processes have been reported as involved in OP-induced hepatotoxicity such as disturbances in the antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 161 publications
(179 reference statements)
6
41
0
3
Order By: Relevance
“…This indicated that the rats were trying to counter SUM-induced oxidative stress that caused an apparent state of oxidative stress, while the SUM group of rats that received HPPJ showed significant protection, which was indicated by the increase in the SOD, GP, and GST enzyme activity. The development of ROS and reactive intermediates following OP pesticides exposure would initiate hepatotoxicity [48,51], which causes huge damage to liver cells and function such as steatosis, chronic hepatitis, aging, inflammatory damage, and ischemic injuries [10,52,53]. The results reported herein showed that SUM affected the hepatocellular integrity.…”
Section: Discussionmentioning
confidence: 83%
“…This indicated that the rats were trying to counter SUM-induced oxidative stress that caused an apparent state of oxidative stress, while the SUM group of rats that received HPPJ showed significant protection, which was indicated by the increase in the SOD, GP, and GST enzyme activity. The development of ROS and reactive intermediates following OP pesticides exposure would initiate hepatotoxicity [48,51], which causes huge damage to liver cells and function such as steatosis, chronic hepatitis, aging, inflammatory damage, and ischemic injuries [10,52,53]. The results reported herein showed that SUM affected the hepatocellular integrity.…”
Section: Discussionmentioning
confidence: 83%
“…Several toxicological and epidemiological studies thus far have shown that OPs can induce oxidative stress (OS) by increasing reactive oxygen species (ROS) and reactive nitrogen species (RNS). These reactive oxygen and nitrogen intermediates can react with biological macromolecules altering their physiological functions [13][14][15]. For instance, the free radicals (FR) can induce depolarization of the mitochondrial membrane, accompanied by generation of ROS and release of numerous pro-apoptotic proteins, such as cytochrome C, which can lead to cell death by apoptosis [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…CPF has been reported to be linked with testicular toxicity in animal models (Babazadeh & Najafi, ; Joshi, Mathur, & Gulati, ) and genital deformities in humankind (Eaton et al, ). Some other deleterious effects have also been demonstrated to be elicited by CPF including immunological anomalies, hepatic dysfunction, genotoxicity, embryotoxicity, cytotoxicity, teratogenicity, cognitive abnormalities, neurodevelopmental disorders, cardiovascular deficits and endocrine system dysfunctions (Ali et al, ; Cunha et al, ; Estevan, Vilanova, & Sogorb, ; Jokanovic, ; Karami‐Mohajeri, Ahmadipour, Rahimi, & Abdollahi, ; Lee, Eriksson, Fredriksson, Buratovic, & Viberg, ; Noworyta‐Glowacka et al, ; Ventura et al, ).…”
Section: Introductionmentioning
confidence: 99%